Emodin, a rising star in the treatment of glycolipid metabolism disorders: a preclinical systematic review and meta-analysis - Yang Xiao; Zhixuan Zhao; Binqin Chen; Jian Sun; Li Wang; Yu Wang; Zheng Nan; Qi Zhang (PeerJ)
Background Rhubarb has a remarkable effect on lowering blood lipid and glucose levels, and its main component, emodin, is an anthraquinone derivative. To elucidate the role and mechanism of emodin in the treatment of type 2 diabetes mellitus (T2DM) and to provide robust evidence for its clinical application, we conducted a systematic review and meta-analysis to assess the influence of emodin on T2DM animal models and the overall therapeutic effect, and further to evaluate its benefits and risks in the management of T2DM. Methods Eight databases were searched from inception to May 2023. Two reviewers extracted the data independently. SYRCLE’s risk of bias tool for animal studies was used to assess the quality of articles. RevMan V.5.4 software and STATA 15.1 software were applied for data analyses. Body weight, serum insulin level (INS), fasting blood glucose (FBG), 2-hour postprandial blood glucose (2hPG, IPGTT/OGTT), insulin tolerance test (IPITT) indicators, total cholesterol (TC), triglycerides (TG), high-density lipoprotein (HDL-c), and low-density lipoprotein cholesterol (LDL-c) were used as outcome measures. Data for outcome messures presented in graphical form were extracted using GetData graphic digitizer software (version 2.26). For outcome indicators with a small number of included studies, we will conduct descriptive analyses. Results Twelve existing studies were included in this meta-analysis, and all of the studies included in this review had a low to moderate risk of bias. The results showed that emodin significantly reduced the glucose and lipid metabolism indicators and effectively lowered body weight and serum insulin levels (FBG, 2hPG(IPGTT/OGTT), IPITT, TG, TC, LDL-c, HDL-c) (P < 0.05). Conclusion Emodin demonstrates significant potential in treating T2DM by reducing FBG, 2hPG (IPGTT/OGTT), IPITT, TC, TG, INS, and body weight in animal models. The therapeutic mechanisms of emodin include enhancing glucose utilization in peripheral tissues, inhibiting glucosidase absorption, alleviating insulin resistance, and strengthening L-type calcium channels. Additionally, emodin shares characteristics with first-line antidiabetic drugs such as metformin, acarbose, and repaglinide, promoting insulin secretion and enhancing cellular sensitivity to insulin. Furthermore, emodin exhibits actions similar to glucagon-likepeptide-1(GLP-1) receptor agonists, suggesting its potential for protecting target organs. Therefore, emodin is a highly promising drug with substantial research and clinical value. However, caution should be exercised due to significant heterogeneity among the studies, and results may evolve with additional research.